The Policy of the Four-Year Vocational High School Program from a Stakeholder Perspective - Tri Haryani; M. Sofwan Efendi; M. Takdir; Kamaludin; Kenzhebayeva A.T. (Jurnal Pendidikan Teknik Sipil, 2025)
Background: The four-year vocational high school (SMK) program was developed to improve the quality of graduates, preparing them to compete in the modern workplace and industry. This study aims to analyze principals' perceptions of the program's objectives, strengths, challenges, and outputs. Methods: A quantitative descriptive method with a survey approach was used. A survey was administered to 68 vocational high school principals across 18 provinces in Indonesia to collect data, and percentages were used for analysis. Results: The program focuses on improving students' technical and non-technical competencies (26.5%), readiness to enter the business and industrial world (22.1%), and national and global competitiveness (17.6%). The program's strengths include depth of competencies (29.4%), longer duration of Field Work Practice (22.1%), and development of maturity and soft skills (17.6%). Parental and student interest is high (55.9%), while the majority of graduates work in their fields of expertise (51.5%) or continue their education (17.6%). Conclusion: Regulatory support includes legal protection, certification, industry partnerships, and curriculum flexibility. Key challenges include industry collaboration, teacher readiness, facilities and infrastructure, regulations and curriculum, and community motivation. These findings provide strategic recommendations for the development of an effective and sustainable four-year vocational high school program.